NUMERICAL MODEL OF MICROWAVE BACKSCATTERING AND EMISSION FROM TERRAIN COVERED WITH VEGETATION - Ferrazzoli, P. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A computational model for estimating microwave scattering and emission from the earth's surface covered with vegetation (MESCAM) has been developed. The model is founded on relevant electromagnetic properties of the vegetation and of the underlying terrain and takes into account multiple scattering both within the vegetation and between vegetation and underlying soil. By selecting the appropriate scattering functions, the backscattering coefficient and the emissivity can be estimated in a wide range of frequencies, for different sensor configurations, and for a variety of terrain and vegetation characteristics. [Vol. 6, No. 1, pp. 175-191 (1991), Special Issue on Applications of High Frequency Methods and Computer Techniques in Electromagnetics]